A systematic review of factors influencing green public procurement in higher education institutions - Santosh Bhandari; Myriam Lopes; Sara Moreno Pires (Discover Sustainability)
Abstract Green Public Procurement (GPP) is emerging as a popular environmental policy instrument that enhances the economy while mitigating environmental impacts. However, the implementation of GPP is recent. According to the European Commission, over 40% of public procurement in the European Union has been influenced by sustainability or environmental considerations. This study analyzes the existing literature on the factors influencing GPP practices in higher education institutions (HEIs), which was limited in earlier literature. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) review method directed this systematic literature review. We selected 72 out of 1719 articles from the Scopus database for the review. An in-depth analysis of the papers resulted in the final selection of 26 articles for the study. The thematic analysis has underlined a key set of themes critical for implementing GPP in HEI, namely, organizational options, relation with stakeholders, GPP knowledge, legal aspects, and economic determinants. Influencing factors related to the organization were the most complex. Furthermore, HEIs should prioritize GPP-related knowledge. Also, they should follow best practices, modify management strategies, and motivate suppliers to comply with GPP requirements. Organizational arrangements for GPP improvement and human resources training could enhance the acceptance rate of GPP practices. Such efficient implementation of GPP in HEIs makes them a positive example for the public sector.